[18F]FDG-PET/CT improves the detection of synchronous malignancies at primary staging of oral squamous cell carcinoma – A retrospective study. Issue 8 (August 2022) - Linz, Christian; Brands, Roman C.; Hackenberg, Stephan; Hartmann, Stefan; Iring, Tobias; Hohm, Julian; Haug, Lukas; Kertels, Olivia; Kircher, Malte; Dierks, Alexander; Buck, Andreas K.; Brumberg, Joachim; et al.
Abstract: The purpose of this study was to show the non-inferiority of [ 18 F]FDG-PET/CT compared with panendoscopy with regards to secondary malignancies of the UADT, and to evaluate the diagnostic performance of PET/CT for detecting synchronous malignancies. Patients with newly diagnosed OSCC and both panendoscopy and [ 18 F]FDG-PET/CT at primary staging were enrolled in this retrospective study. The accuracy in detecting synchronous malignancies was assessed for both modalities, and their diagnostic measures for the detection of malignancies within the UADT were compared. Histopathological analysis and clinical follow-up served as reference standards. In total, 182 patients were enrolled in this study. Eighteen patients (9.9%) had in total 22 synchronous malignancies, of which eight were located within the UADT. [ 18 F]FDG-PET/CT detected all malignancies within the whole body (sensitivity: 100%) and yielded false-positive results in four cases (specificity: 97.6%). Sensitivity ([ 18 F]FDG-PET/CT: 100% vs panendoscopy: 87.5%), specificity (99.4% vs 100%), negative predictive value (100% vs 99.4%), and positive predictive value (88.9% vs 100%) for detecting secondary UADT malignancies did not differ between modalities (all p = 0.32). Within the limitations of the study it seems that [ 18 F]FDG-PET/CT detects synchronous malignancies of the UADT with an accuracy comparable to panendoscopy, and enables highly sensitive whole-body tumor screening in patients with newly diagnosed OSCC. This could be a relevant factor for therapeutic decision making in clinical routine.